Similarities and differences among fluid milk products: traditionally produced, extended shelf life and ultrahigh-temperature processed. (June 2013) - Grabowski, NT; Ahlfeld, B; Brix, A; Hagemann, A; von Münchhausen, C; Klein, G
Extended shelf life milk is a relatively new kind of fluid milk, generally manufactured by high-temperature treatment and/or micro-filtration. Being advertised as 'pasteurized milk with an extended shelf life', its flavour, compositional quality and labelling was questioned. Extended shelf life (high-temperature treatment), pasteurized ('traditionally produced') and ultrahigh-temperature milk were, therefore, compared at the beginning and end of shelf life. In triangle tests, panellists distinguished clearly between all products. High-temperature treatment milk's flavour was closer to ultrahigh-temperature and traditionally produced milk in the beginning and at the end of shelf life, respectively. Physicochemically and bacteriologically, all three types could be distinguished. Since 'extended shelf life' comprises many process varieties (each affecting flavour differently), consumer information and appropriate package labelling beyond 'long-lasting' is necessary, e.g. by mentioning the heat treatment applied.